An empirical study of regulatory capture in Kenya's maize seed sector - Van Dycke, Lodewijk Guido K.; Mawia, Harriet; Rutsaert, Pieter; Donovan, Jason A. (Walter de Gruyter GmbH, 2024)
In sub-Saharan Africa, public sector breeding programs depend on local seed companies to deliver new maize varieties to farmers. Such varieties are needed to adapt cropping systems to climate change. While dozens of small and medium seed companies have emerged in the last two decades, the maize seed market in Kenya remains dominated by the parastatal seed company Kenya Seed Company, with multinational seed companies making major inroads. We assess whether parastatal and multinational seed companies have captured Kenya’s seed laws to the detriment of local small and medium seed companies (‘regulatory capture’), negatively effecting competition and the capacity of local companies to introduce new varieties in the hybrid maize seed market. We conducted in-depth interviews based on legal clauses with maize seed companies active in Kenya, as well as interviews with regulators and stakeholders. Results show that local companies do not feel disadvantaged compared to their multinational counterparts or the parastatal. However, all of them are wary of the entry of new actors. Moreover, through excessive procedures, the Kenyan government keeps a sovereign grasp over the seed sector. Despite frustrations with some of these excessive procedures, seed companies felt comfortable in the protective environment of the Kenyan seed market and were generally happy with the technical aspects of Kenya’s seed laws, which are based on international norms. We suggest some improvements to make Kenyan seed laws more conducive to varietal turnover, in line with seed companies’ suggestions and taking into account the political sensitivities of the Kenyan government.